PUSAT KEGIATAN DAN PENDIDIKAN ANAK- ANAK PENYANDANG AUTIS DI MAKASSAR - Rizal, Syamsu; Rahman, Sitti Aisyah; Mutmainnah, Mutmainnah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2014)
The Autism children are who experience barriers to the development of speech and occupational behavio . Recent research shows one in 150 children in Indonesia are now suffering from autism . Comparison of children with autism with normal children around the world reached 1 : 100. In South Sulawesi , no less than 1,000 children under the age of five years ( toddlers ) affected with autism . In order to develop an autistic child is required pontesi container that can reflect some of the child protection legislation and government programs are compulsory nine years . Containers must be based on a system of activities and special education for children with autism . The goal is to identify children with special needs with emphasis on healing the child to be able to blend in social life . From the analysis of the need for container have been the right location and in accordance with the designation of the central building and educational activities of children with autism in Makassar, which is in Tamalanrea . This design results of the analysis combined with reference to relevant theory . Shape design philosophy begins with geometric forms and cylinder block . The shape of the building the appearance of an effect on the processing site and the structure and materials used , while also considering other factors such as utilities and supplies bangunanannya.